Strategi Hubungan Masyarakat dalam Komunikasi Dua Arah dengan Wali Murid di Lembaga Pendidikan - Arrifah Putri Nadila; Ula Masrurotuz Zahro (Center for Studies in Advanced Science, 2025)
Interactive communication is an effective two-way communication model between individuals in educational institutions. A good strategy is needed to have a positive impact on the institution. This study aims to find out the efforts of public relations communication, the communication media used by public relations, and the interactive communication strategy of public relations to the parents of students at MI Ma'arif Penanggungan. The research method used is qualitative with case study techniques. Data was collected through the results of literature studies, interviews, observations, and documentation. The data analysis technique consists of three stages, namely data condensation, data presentation, and conclusion drawn. The results of the study showed: (1) public relations communication efforts to the parents of MI Ma'arif Penanggungan students are to provide and provide institutional information and are open to questions and answers with the parents of students; (2) public relations communication media in the form of social media, print media, and websites; and (3) public relations interactive communication strategies to students' parents, namely mastering communication techniques, utilizing social media, providing the best service in terms of time, and holding deliberations.